Aliphatic tertiary amine catalysed urethane formation – a combined experimental and theoretical study. Issue 34 (23rd August 2022) - Waleed, Hadeer Q.; Csécsi, Marcell; Konyhás, Vivien; Boros, Zsanett R.; Viskolcz, Béla; Fejes, Zsolt; Fiser, Béla
Abstract : A kinetic and mechanistic investigation of the alcoholysis of phenyl isocyanate (PhNCO) using stoichiometric butan-1-ol (BuOH) in acetonitrile in the presence of different tertiary amine catalysts was performed. Abstract : A kinetic and mechanistic investigation of the alcoholysis of phenyl isocyanate (PhNCO) using stoichiometric butan-1-ol (BuOH) in acetonitrile in the presence of different tertiary amine catalysts was performed. The reaction mechanisms in the absence and presence of experimentally applied catalysts were described by using the G3MP2BHandHLYP composite method. The apparent activation energies obtained from the calculations were in good agreement with the experimental data (ΔΔ E = <2 kJ mol −1 ). Both experimental and theoretical results proved the important effect of tertiary amine catalysts on urethane formation. These results can aid in polyurethane catalyst design and development.